Study guides

☆☆

Q: What is -3x 9x equal?

Write your answer...

Submit

Still have questions?

Related questions

3x. 15x - 9x = 6x 9x - 6x = 3x 6x - 3x = 3x 3x - 3x = 0

42069

-3x+9x can be simplified to 6x

12

5-ish

If you mean 9x^2-24x+16 then yes it can because its discriminant is equal to zero and it is (3x-4)(3x-4) when factored

factor out a 3x 3x(x-3)=3x2-9x

9x2-9x-10 = (3x+2)(3x-5) when factored

Assuming you mean 3x - 2 = 9x - 5...3x - 2 = 9x - 53x + 3 = 9x3 = 6x0.5 = x

Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x

3x + 3x + 3x = 3* (3x) = 9x

Apply the Distrubutive Property twice as you do when multiplying two-digit numbers Use the FOIL methed First Inner Outter Last. In the equation (3x + 4)(9x + 1) you get. (3x)*(9x) + (3x)*1 + (9x)*4 + 4*1 Now you multiply. 3x*9x = 27x^2 3x*1 + 9x*4 = 3x + 36x = 39x 1*4 = 4 So your entire answer is (3x)*(9x) + (3x)*1 + (9x)*4 + 4*1 = 27x^2 + 39x + 4